OCHRONA ŚWIATŁA I WIDOKU W PRAWIE RZYMSKIM I TRAKTACIE URBANISTYCZNYM JULIANA Z ASKALONU - Skalec, Aneta (Zeszyty Prawnicze, 2016)
Protection of Light and of View in Roman Law and Julian of Ascalon’s Treatise Summary Problems of vicinity were a subject of regulations starting from the time of classical Greece, but the most complete text relating to this question is Julian of Ascalon’s Treatise, a work written at the end of the V or during the VI century in Palestine by an architect known by the name of Julian. One of the aspects regulated by this text, as well as, in a similar way, by Roman law, was the protection of light and of view. In Roman law light was protected by a series of special servitudes: ius altius tollendi aut non tellendi, ius ne luminibus officiator, servitus luminum and servitus luminis imittendi. An analogy to the latter is also found in the treatise. According to the above sources also the view (prospectus) was protected. In the constitutions of Roman emperors known from the Code of Justinian we find only protection of the sea view, but Julian also regulated protection of the view on mountains, gardens and public paintings and he probably based his regulations on other unknown constitutions. A subject connected with view and light was the typology of windows. In both texts there existed a legally relevant distinction between panoramic windows and ones that served only for lighting, because the first could be made only when certain conditions were met, and the second could be constructed only at a certain height.